A Model for Fostering Labor Productivity and Wage Management: A Long-Term Outlook to 2034 - Evgeniy V. Kostyrin; Loua Moussa Pascal; Dmitriy Kostyrin (Emerging Science Journal, 2026)
This research aims to develop a complex system of managerial decision-making support, which includes an economic-mathematical model of maximizing the salary share in the company’s revenue, consistent with the financial interests of business owners and the state, analyzing the sensitivity of the maximum wage share to key parameters of the model, and developing software based on MS Excel and PTC Mathcad Prime 3.1. The research methodology included system analysis, non-linear programming, sensitivity analysis, and dynamic system modeling linking time-related changes in wages, labor productivity, enterprises’ reinvestment, and financial stability. Modeling results showed that a balanced policy allows employees to increase wages by 59.83% and net profit by 2.97. The return on sales increased by 2.28 times, and government revenues from taxes and social contributions increased by 58.78%. The maximum sustainable share of wages in revenue reaches 54.73%, which is 9.83% higher than the base indicator. The novelty of the research lies in the development and practical implementation of an economic and mathematical model that maximizes the share of wages in the company’s revenue while balancing the financial results of employees, owners, and the state within the framework of the Russian fiscal system. JEL Classification: C44, I11, J31, M21.